Tanzania’s diaspora engagement: The need for a paradigm shift in diaspora engagement and investment policies - Ambrose T. Kessy; Hildebrand E. Shayo (Research in Globalization, 2022)
African countries' attitudes towards their diasporas, including Tanzania, have altered substantially during the past decade. Diasporas were not considered as a strategic resource that countries of origin might leverage for growth. This is no longer the case. Diasporas are widely perceived favourably as productive actors: as countrymen and women living abroad who can help their homelands thrive and many countries have successfully engaged and integrated diaspora issues into the process of national development. In this case, this article reviews key policies and initiatives adopted by the Government of Tanzania (GoT) to establish diaspora engagement in the national development policies and plans. It attempts to interpret these efforts within the framework of Tanzania’s modern social, economic, political, and cultural circumstances. Tanzania's experience illustrates a breadth of measures aimed at increasing diasporas’ participation in national economic endeavors. While these initiatives are appreciated, some significant challenges remain unsolved. The paper concludes by arguing that Tanzania has not been too late to re-engage with the diasporas and more efforts need to be made. Some recommendations are offered to improve the effectiveness of current measures to assist policymakers in enacting favorable policies that will maximize the diaspora's potential for national development.